A detailed description of Simulium (Meilloniellum) adersi (Pomeroy) from Mayotte, Comoro islands, with comments on bionomics and biogeography (Diptera: Simuliidae) - Craig, Douglas A.; Mary-Sasal, Nathalie (Zootaxa, 2013)
All stages of Simulium (Meilloniellum) adersi (Pomeroy) from Mayotte, Comoro archipelago are described in detail. This species is widespread on the African mainland and in Madagascar; morphological divergences from African material point towards the Mayotte entity being a separate, but closely related species. Biology of the species overall is reviewed and brief comments are made regarding habitats and biogeography of the Mayotte material.